Estudo da quantidade de jogadores em jogos reduzidos de handebol: mudança na dinâmica técnica e tática - CLEMENTE, Filipe Manuel (2014)
The aim of this study was to verity the effects of different formats of handball game (2 vs 2, 3 vs 3 and 4 vs 4) on technical and tactical performance of Physical Education students. Eight male students (18.25 ± 1.04 years old) participated in this study. It was possible to verify significant statistical differences in the number of ball contacts, number of shoulder passes and shoulder passes completed. It was also possible to verify significant statistical differences in the organized attack and counterattack. Therefore, it was possible to conclude that smaller formats of small-sided handball games allows to increase the technical and tactical actions, thus being more appropriated to early stages of learning.